Influence of salts, anion polyacrylamide and crude oil on nanofiltration membrane fouling during desalination process of polymer flooding produced water - Zhang, Ruijun; Shi, Wenxin; Yu, Shuili; Wang, Wei; Zhang, Zhiqiang; Zhang, Bing; Li, Li; Bao, Xian (Desalination, 2015)
The effective management of polymer flooding produced water (PFPW), co-produced in the process of polymer flooding oil extraction, will become a subject to solve urgently. To study membrane fouling properties, a commercial NF membrane (NF90) was adopted to treat model PFPW in this work, with different kinds of salt, anion polyacrylamide (APAM) and crude oil as target foulants. AFM, SEM-EDS, ATR-FTIR and contact angle were employed to analyze various membrane autopsies. The results showed that the membrane fouling was dominantly induced by APAM, as well as salts and crude oil. Various mutual influences between ions and APAM including charge screening, complexation, molecule coiling up and anti-scaling effect would aggravate or mitigate fouling in different combinations. The hydrophilic APAM could produce a “shielding effect” against crude oil because of its rapid adhesion on membrane surface under the strong hydrogen binding and complexation assisted by calcium. Membrane fouling induced by the three target foulants could improve salt rejection by strengthening size exclusion. In addition, the Donnan effect caused by APAM and nonpolar action caused by crude oil can also contribute in salt removal. Finally, fouling mechanism was proposed and some suggestions were put forward. •Fouling mechanism when treating PFPW with NF membrane is proposed.•Mutual influence between different foulants is revealed.•Effect of various foulants on desalination performance is analyzed.•Some research suggestions are given accordingly.